Fostering mutual understanding: Indonesian language workshop at STS 3.0 / Noraziah Mohd Amin, Marni Jamil and Nur Afiqah Ab. Latif - Mohd Amin, Noraziah; Jamil, Marni; Ab. Latif, Nur Afiqah (UiTM Global @ Office of International Affairs, 2024)
Dr. Ridha Hasnul Ulya from Universitas Negeri Padang (UNP), Sumatera Barat, Indonesia, was invited as a speaker to teach the Indonesian language to the participants of a school holiday programme named, “Sparkle Through Speech 3.0 (Digital Dialogue: Mastering Communication Skills)” or STS 3.0. The session took place on 15 February 2024, at Pusat IT, Perpustakaan Tun Abdul Razak (PTAR), Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, Malaysia. Dr. Ridha is from the Department of Indonesian Language and Literature, Faculty of Language and Art, UNP. He earned a Bachelor of Education in Indonesian Language and Literature from UNP. His research interests include culture, linguistics, and language learning, and he has contributed to various academic publications in these areas.